Pertumbuhan dan Kandungan Pigmen Tanaman Keladi (Caladium bicolor Aiton Vent) pada Tanah yang Merkuri (HgCl2) - Riza Linda, Apriana Anania, Mukarlina, (Jurnal Protobiont, 2017)
Mercury is one of the heavy metals and is toxic which causes a decrease in pH and soil fertility. Keladi (Caladium bicolor) is able to grow and adapt to heavy metal contaminated soil because it has a tolerance mechanism and contains antioxidant pigments. This research aims to determine the effect of mercury on the growth and the content of C. bicolor pigment. This research was conducted from January 2017 until March 2017 at Greenhouse and Biology Laboratory of the Faculty of Mathematics and Natural Sciences of Tanjugpura University Pontianak. The research was a completely randomized design with 5 replications consisting of control, concentrations HgCl2 300, 350, 400 and 450 ppm. The results showed that the concentrations of HgCl2 at 350, 400 and 450 ppm decreased the chlorophyll pigment content, wet weight and dry weight of C. bicolor. The concentrations of HgCl2 at 300 ppm increases the anthocyanin pigment content and HgCl2 had no significant effect on carotenoid pigment content.